Community Development in the Lao Mining Sector - World Bank (Washington, DC, 2013)
The purpose of this Briefing Note is to provide background information and analysis on the new legal requirement and relevant information and experience pertaining to community development funds in the mining sector internationally and in Lao PDR. This Briefing Note is intended to inform discussion at the Conference on Mining and Community Development in Lao PDR: Community Development Funds to be held in Vientiane and Phu Kham, 19-23 September 2011. The Briefing Note draws heavily on information from a number of existing World Bankpublications including: Lao PDR Development Report - Natural Resource Management for Sustainable Development: Hydropower and Mining and relevant background papers which examine themes of social impact mitigation andbenefit sharing. Mining Foundations, Trusts and Funds A Sourcebook which reviews developing country experience of mining sector foundations, trusts and funds. Sharing Mining Benefits in Developing Countries: the experience with foundations, trusts and funds a publication from the World Bank Oil, Gas, and Mining Policy Division (SEGOM) that summarises developing country experiences.The Briefing Note also draws on a number of interviews conducted with key government agencies including the Department of Mines (DOM), Ministry of Energy and Mines; Department of Environment Impact Assessment (DESIA), Ministry of Natural Resources and Environment; Department of International Cooperation (DOIC), Ministry of Planning and Investment; Department of External Finance, Ministry of Finance; Poverty Reduction Fund (PRF) as well as the two largest mining operators: Phu Bia Mining (PBM) and Lane Xang Minerals Limited(LXML). The intended audience of this note is policy makers, members of the development community and representatives from the private sector (mining companies and consultants).